Segundas núpcias: a viuvez e a construção moral dos matrimônios no maranhão setecentista (1761-1799) - SOUSA, Diele Amanda Marques de (2019)
This study aims to understand the conception about marriages in eighteenth century Maranhão. Highlighting, above all, the conjugal relations considered unregulated, that is, the relations of concubinage. For this analysis, the documents used were the Autos de Justificação de Viuvez (located in the Public Archive of the State of Maranhão - APEM), which constitute some of the processes conducted by the bishopric (Chamber Ecclesiastica) of Maranhão, in the seven hundred. Thus, this dissertation was directed to the widows and widows who threatened the sacrament of matrimony, before justifying their widowhood. Through the First Constituições do Arcebispado da Bahia (1707), which were adapted according to the colonial reality, based on the redefinition of the sacrament of marriage by the Council of Trent, it was possible to perceive how the Ecclesiastical Judgment of Maranhão intervened in the daily life of the population and, moreover, what were the punishments committed by devotees of that religious norm.